If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 5x + -29 = 0 Reorder the terms: -29 + x + 5x = 0 Combine like terms: x + 5x = 6x -29 + 6x = 0 Solving -29 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 6x = 0 + 29 Combine like terms: -29 + 29 = 0 0 + 6x = 0 + 29 6x = 0 + 29 Combine like terms: 0 + 29 = 29 6x = 29 Divide each side by '6'. x = 4.833333333 Simplifying x = 4.833333333
| 6/12=w/3 | | p^4(4p^2q^6)^1/2 | | T-2/5 | | 4x^2-27x+98=0 | | -x*x*x+(x+5)*(x+5)*(x+5)=485 | | 11=(y/-2) | | (-14/7)=11x | | 2m^2-4m-3= | | 36-25n^2=0 | | 35-s=20 | | (x/3)-(2/9)=(-8/9) | | Y=12+.033x | | 3(x-5)+3x=4x-27 | | 14=3s-4(28-s) | | 90/(v-1)=15 | | Y-2=4(3+5) | | 90/v-1=15 | | 55-2x=-51-5x | | -2x-3y=48 | | (6m-10)/2m | | y+7=6(x+8) | | 40+10P=100-20P | | 5x*x+15x=130 | | 4n^2+12n-24=0 | | -6u-28=o | | 28/(q-3) | | n^2-9n+11=0 | | 15x-5-4=2 | | 34y+2=6 | | 4m^2-12m-2=0 | | 5b^2=25 | | V^2+16-8v= |